Evaluación de la abundancia de Ceratopogonidos (Díptera) polinizadores de Cacao (Theobroma cacao L.) en la hojarascada de 7 árboles de sombra, Talamanca-Costa Rica - Mavisoy M., Karol H. (2015)
In the community of Watsi, Bri-Bri Indigenous Town, southwest of Costa Rica, Canton of Talamanca, Limon Province, located at 9 ° 37 '26.3 "N and 82 ° 52' 53.1" W, with a height between 70 and 180 masl, the abundance of genus Forcipomyia, Atrichopogon, Dasyhelea (Diptera: Ceratopogonidae) insects pollinators of cocoa was assessed and its main natural enemies Dermaptera, Chillopoda and Formicidae, we analyzed the litter of banana Musa AAA, laurel Cordia alliodora, Rambutan Nephelium lappaceum, guaba Inga sp, pejivalle Bactris gasipaes, avocado Persea americana, apple water Syzygium malaccense type shade used and cocoa Theobroma cacao not shaded as control treatment. Litter samples were taken of each species, the larvae were count and adults were breeding in emergency traps under moist controlled conditions, the valued variables were number of Ceratopogonidae, natural enemies, percentage of shade and sample`s wet weight. Data analysis was performed using Friedman's nonparametric test and multivariate analysis. We found that the most litter studied offered suitable conditions for breading of larvae and adult insects Forcipomyia genus pollinators of cocoa. Key words: percentage of shade, wet weight, natural enemies, agroforestry systems